Leprosy: a suspected diagnosis in a non-endemic area. Case series and literature review - Mendez-Guerra, Carolina (2020)
Leprosy (Hansen’s disease) is a chronic granulomatous condition caused by Mycobacterium leprae, a microorganism that affects the skin and Schwann’s cells. Making a diagnosis of this condition is difficult in non-endemic areas because of low clinical suspicion. During the 2012-2019 time period, three cases of Hansen’s disease were diagnosed and treated in the ID service of Dos de Mayo Hospital. The average time history of the disease was 4 years. Patients started their condition with the appearance of pruriginous papular lesions affecting specific body regions, progressing to generalized nodular lesions. Paresthesia and tactile, thermal, pain, and vibratory hypoesthesia were found. These manifestations later progressed to anesthesia. Diagnosis was made through bacilloscopy in lymphatic fluid and skin node biopsy. Clinical features for each patient are also described. We emphasize the importance of clinical suspicion for diagnosing this unattended disease in non-endemic areas.